2013
DOI: 10.3892/mmr.2013.1509
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of tissue angiotensin II increases with severity of experimental pancreatitis

Abstract: Abstract. Necrotizing pancreatitis is a serious condition that is associated with high morbidity and mortality. Although vasospasm is reportedly involved in necrotizing pancreatitis, the underlying mechanism is not completely clear. In addition, the local renin-angiotensin system has been hypothesized to be involved in the progression of pancreatitis and trypsin has been shown to generate angiotensin II under weakly acidic conditions. However, to the best of our knowledge, no studies have reported elevated ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Ang II and its receptors AT1 and AT2 serve important roles in the pathogenesis of AP, whereas Ang 1–7 has been reported to act as an antagonist that inhibits inflammation ( 16 , 17 ). In addition, recent studies have demonstrated that Ang II can regulate TLR4 expression in order to modulate inflammation and other associated functions ( 18 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ang II and its receptors AT1 and AT2 serve important roles in the pathogenesis of AP, whereas Ang 1–7 has been reported to act as an antagonist that inhibits inflammation ( 16 , 17 ). In addition, recent studies have demonstrated that Ang II can regulate TLR4 expression in order to modulate inflammation and other associated functions ( 18 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Frozen tissue samples were homogenized in 0.1% NHCl and 5% urinastatin saline at 4°C. The homogenate was centrifuged for 30 min at 4°C at 10,000 g , with the supernatant collected and analyzed with an enzyme‐linked immunosorbent assay 25 .…”
Section: Methodsmentioning
confidence: 99%